Minimum Wages and Labor Supply in an Emerging Market : The Case of Mauritius - Asmal, Zaakhir; Bhorat, Haroon; Kanbur, Ravi; Ranzani, Marco; Paci, Pierella (World Bank, Washington, DC, 2018)
This paper investigates the effect of multiple minimum wages, known as remuneration orders, on employment and working hours in Mauritius. Using data between 2004 and 2014, the analysis indicates that a 10 percent increase in the minimum wages brings about a slightly positive effect on employment in the covered sector, with an estimated employment elasticity of 0.113, which is within the range of elasticities found in previous studies of employment effects of minimum wages in low- and middle-income countries. The positive employment effect of minimum wages is also associated with a 2.3 percent increase in average working hours for men but a 1.8 percent decline in average working hours for women in the covered sector. In the uncovered sector, the significant positive effect along the intensive margin, estimated at 4.2 percent, is driven by changes in labor supply among men.